A Low Complexity Asynchronous UWB TDOA Localization Method. (4th October 2015) - Song, Liyuan; Zou, Hongliang; Zhang, Tingting
Abstract : Impulse-radio ultrawideband (IR-UWB) is a promising technique for indoor localization due to its high accuracy and robustness against multipath interferences. In this paper, to deal with the synchronization challenges among anchors in traditional time-difference-of-arrival (TDOA) localization systems, we propose an asynchronous TDOA (ATDOA) localization method. Based on the ranging error model, we derive the theoretical lower bounds as the performance metrics of localization accuracy. Compared with the ideal TDOA method, ATDOA degrades on localization accuracy for eliminating the high accuracy synchronization requirements, which is pretty much attractive in energy and complexity limited scenarios. Based on the performance analysis, we show that there exists optimal anchor deployment in ATDOA that minimizes the localization errors. We also formulate the relationship between this optimal deployment and the size of the covered area, which is meaningful in both theoretical analysis and practical system designs.